2017
DOI: 10.2967/jnumed.116.187971
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Dual-Labeling Scaffold That Retains Agonistic Properties for Somatostatin Receptor Targeting

Abstract: Fluorescence-guided surgery is an emerging imaging technique that can enhance the ability of surgeons to detect tumors when compared with visual observation. To facilitate characterization, fluorescently labeled probes have been dual-labeled with a radionuclide to enable cross-validation with nuclear imaging. In this study, we selected the somatostatin receptor imaging agent DOTATOC as the foundation for developing a dual-labeled analog. We hypothesized that a customized dual-labeling approach with a multimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Therefore, efficacy is dependent upon the specificity of the agent for its target and its overexpression in tumor tissue. We previously showed SSTR2-mediated uptake of 64 Cu-MMC(IR800)-TOC in vitro and in vivo, where competition with octreotide strongly reduced uptake in SSTR2-expressing tumors (36). In a subsequent study with 68 Ga-MMC(IR800)-TOC, we demonstrated selective in vitro uptake by SSTR2-expressing cells that was 20-fold higher than cells that lacked the receptor, as well as a 16-fold reduction in uptake when coincubated with octreotide (12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efficacy is dependent upon the specificity of the agent for its target and its overexpression in tumor tissue. We previously showed SSTR2-mediated uptake of 64 Cu-MMC(IR800)-TOC in vitro and in vivo, where competition with octreotide strongly reduced uptake in SSTR2-expressing tumors (36). In a subsequent study with 68 Ga-MMC(IR800)-TOC, we demonstrated selective in vitro uptake by SSTR2-expressing cells that was 20-fold higher than cells that lacked the receptor, as well as a 16-fold reduction in uptake when coincubated with octreotide (12).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor‐to‐background ratios 1 h after injection were moderate for the muscles and low for blood. Other studies with SSTR2‐targeting hybrid probes observed similar values 3–4 h after injection, [14b,18a] which could be improved when imaging at later time points, such as 24 or 48 h after injection with 67 Ga [18c] …”
Section: Resultsmentioning
confidence: 63%
“…According to the PET/MRI and biodistribution data, the clearance route is predominantly renal with a high uptake in the kidneys (∼30 % IA g −1 ). Attaching a fluorophore to 68 Ga‐DOTATATE usually causes higher renal uptake compared to the dye‐free 68 Ga‐DOTATATE, [21,23] leading to values of up to 70 % IA g −1 [14b,18a] . The same applies, usually to a smaller extent, for the uptake in the liver, which is also influenced by nonpolar structural moieties as typically given by fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…The development of bivalent radiotracers to target several receptors concomitantly expressed could be of interest to improve targeting [ 237 ]. Similarly, improved detection and sensitivity could be achieved using bimodal agents [ 238 ]. Besides, the clinical success for radiolabeled somatostatin analogs both with diagnostic and therapeutic radionuclides paved the way for new promising peptide derivatives, such as bombesin, neurotensin, or CXCR4 ligands, and, in a similar way, PSMA ligands, for cancer theranostics [ 49 , 233 , 239 , 240 ].…”
Section: Future Prospectsmentioning
confidence: 99%